Monitoring the agri-food system in Myanmar: Agricultural input retailers – June 2021 survey round - Myanmar Agriculture Support Activity (International Food Policy Research Institute, 2021)
To understand the effects of recent disruptions on Myanmar’s agricultural input sector, a phone survey of input retailers was conducted in June 2021. Key findings: ▪ Prices of key agricultural inputs–fertilizer, pesticides, maize seed, and vegetable seed– are higher in June 2021 compared to June 2020 during the first wave of COVID-19. Onaverage, urea fertilizer prices are 52 percent higher and compound fertilizer prices are 29 percent higher. ▪ Reported input sales are much lower in June 2021 than in June 2020, with fertilizer sales volumes 48 percent lower on average and maize seed 39 percent lower on average. ▪ There continue to be widespread business disruptions stemming from political instability. Issues in the banking sector are the biggest disruption for 75 percent of our sample, though 84 percent also reported higher transportation costs. ▪ Nearly two-thirds of interviewed input retailers have offered inputs on credit to farmers this monsoon season. However, 79 percent intend to decrease their total value of credit compared to last year. Only 22 percent of input retailers reported that farmers in their area received MADB loans for the 2021 monsoon season. ▪ During the third wave of COVID-19 in Myanmar, adoption of safety practices is much lower than during the first wave. Sixty percent of input retailers adopted at least one practice, but only 44 percent were regularly washing their hands and only 47 percent were wearing masks. ▪ Higher input costs and lower access to credit will likely result in lower purchased input use and lower yields for monsoon crops. Measures to support combine harvesting and post-harvest management (e.g., drying) could help minimize further yield loss.